Analysis of transient natural convective flow of a nanofluid in a vertical tube - Jha, Basant K.; Chitumu, Ali J.; Oni, Michael O. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis into the transient natural convective flow of a nanofluid in a vertical tube is made. The governing equations of momentum, heat transfer and nanoparticle volume fraction are deduced, and the influence of the thermophoresis parameter and Brownian motion is incorporated.
Keywords: nanofluid; transient; natural convection; heat transfer; vertical tube